2017
DOI: 10.1002/ecs2.1901
|View full text |Cite
|
Sign up to set email alerts
|

On the controls of abundance for soil‐dwelling organisms on the Tibetan Plateau

Abstract: -S. He. 2017. On the controls of abundance for soil-dwelling organisms on the Tibetan Plateau. Ecosphere 8(7):e01901. 10. 1002/ecs2.1901 Abstract. After decades of research, we are starting to understand more about why the number of species varies from place to place on the planet. However, little is known about spatial variation in abundance, especially for soil-dwelling organisms. In this study, we aimed to disentangle the relative influences of climatic factors, soil properties, and plant diversity on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Although at Blue Rock mining site, a significant moderate positive correlation was recorded between soil pH and species richness, we also observed a non-significant positive correlation between soil pH and arthropod abundance. These results support Zhao et al (2017) who found a weak positive correlation between arthropod abundance and soil pH. Sayer et al (2010) reported that phosphorus, calcium and sodium concentrations are vital in shaping the diversity of arthropods, while the concentrations of sodium and magnesium are vital for arthropod abundance.…”
Section: Surface-active Arthropods and Soil Chemical Propertiessupporting
confidence: 82%
“…Although at Blue Rock mining site, a significant moderate positive correlation was recorded between soil pH and species richness, we also observed a non-significant positive correlation between soil pH and arthropod abundance. These results support Zhao et al (2017) who found a weak positive correlation between arthropod abundance and soil pH. Sayer et al (2010) reported that phosphorus, calcium and sodium concentrations are vital in shaping the diversity of arthropods, while the concentrations of sodium and magnesium are vital for arthropod abundance.…”
Section: Surface-active Arthropods and Soil Chemical Propertiessupporting
confidence: 82%
“…Therefore, it is hard to estimate the net effect of soil animal on the decomposition. However, nematode and arthropod abundance in the Tibetan alpine meadow soil is relatively low compared to other ecosystems such as forests 4446 , and the effect of soil animals may also be low in our study.…”
Section: Discussionmentioning
confidence: 53%
“…Community ecologists are increasingly recognizing the strong, positive relationship between SOC and plant diversity (Chen et al 2018, Yang et al 2019), and studies of flora and fauna populations also benefit from understanding SOC abundance. For example, the abundance of soil‐dwelling invertebrates is strongly driven by SOC contents across natural and agro‐ecosystems (Wang et al 2016, Zhao et al 2017). Studies of soil microbial populations and communities are also invaluable for understanding the fundamental mechanisms governing how soils can feed back to climate at a large scale.…”
Section: Diverse Scientific Disciplines Benefit From Augmenting Soc Dmentioning
confidence: 99%